Look back in anger - Weidner, Paul.; Osborne, John, 1929-1994.; Asolo Theater Festival (Organization : Sarasota, Fla.); Richard L. Coe Theater Programs Collection (Library of Congress) (1968)
Asolo Theater Festival, the state theater, 1968 winter season. The Asolo Theater Festival production company, the acting company and playbill for the winter season including "Henry Fourth, Part 1," Shakespeare, "Servant of Two Masters," Goldini, "Tartuffe," Moliere, "J.B.," MacLeish and "Look Back in Anger," Osborne. "Look Back in Anger," by John Osborne, directed by Paul R. Weidner, senery by Ray Perry, costumes by Joy Breckenridge, lighting by Richard C. Evans, original music by Stephen Smith.
Asolo Theatre Festival, 1968 winter season.
Title devised by Library staff.
Cast: Robert Britton, Charlotte Moore, Polly Holliday, Anthony Heald, David O. Petersen.
LC copy shelved under: Asolo Festival Theater.
With: Henry the Fourth, Part 1 / William Shakespeare. Issued together.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Souvenir programs -- Florida -- Sarasota; Theater programs -- Florida -- Sarasota; Souvenir programs -- 1968.; Theater programs -- 1968.